Mammary Analog Secretory Carcinoma of the Parotid Gland. (23rd August 2013) - Kozin, Elliot D.; Remenschneider, Aaron K.; Naunheim, Matthew; Carter, Margaret; Meier, Josh; Vanderlaan, Paul; Frankenthaler, Robert A.
Abstract : Objectives: 1) Describe newly classified salivary gland tumor, mammary analog secretory carcinoma (MASC) of the salivary gland. 2) Present a patient with a right parotid mass with pathology consistent with MASC and discuss our institution's diagnostic and therapeutic approach. Methods: We identified a rare case of MASC of the parotid gland. We conducted a PubMed literature review on MASC with reports in the pathology and otolaryngology literature. Results: A 58‐year‐old female presented to our clinic after noticing swelling in her right cheek. An MRI of the neck found a well‐encapsulated benign appearing parotid mass measuring 3.2 × 2.2 × 3.1 cm. A fine‐needle aspiration was performed and was concerning for high‐grade carcinoma, with a differential diagnosis including acinic cell carcinoma and mucoepidermoid carcinoma. She underwent a parotidectomy and modified radical neck dissection. Histologic evaluation was consistent with MASC. Subsequent FISH testing demonstrated the characteristic t(12;15) ETV6‐NTRK3 translocation, confirming the diagnosis of MASC. Conclusions: First described in 2010, MASC of the salivary gland is a newly described pathologic diagnosis. It has few reports in the literature. Our case raises the question as to when to consider MASC in the differential diagnosis based on imaging, FNA, and final pathology, including de‐differentiation from acinic cell carcinoma. Further study is needed to best delineate appropriate diagnostic and therapeutic approach for the otolaryngologist for this emerging pathologic entity.